ONLINE BUYING AND SELLING WITH DROPSHIPPING SYSTEM IN ISLAMIC ECONOMIC PERSPECTIVE - Aula Izatul Aini; Komarudin A.; Dwi Julaidah (International Conference on Humanity Education and Society (ICHES), 2023)
The stretching of online buying and selling transactions is growing and becoming a trend for many people, one of the online buying and selling systems that is currently in vogue is the dropshipping system. The purpose of this study is to find out how the practice of buying and selling online with the dropshipping system at Bina Abadi Fashion Bangorejo Banyuwangi in the perspective of Islamic Economics. This study uses a qualitative method with a case study research type. The data analysis technique used in this study is an interactive model. The results of this study are that Bina Abadi Fashion in its implementation fulfills the pillars and conditions of buying and selling in the Islamic economy. Consent is carried out verbally or in writing stating that there is a sale and purchase agreement between the consumer and the dropshipper and the dropshipper and the supplier. Goods that are traded are at the responsibility of the supplier and are characterized based on existing specifications through pictures or photos. The perpetrators of buying and selling already have skills in buying and selling transactions, and when the goods do not match the order or do not match those specified, the supplier will make compensation on condition that there is accompanying evidence. The contract used is bai' maushufun fi dzimmah, namely buying and selling which is still suspended.